A study of soft-material mechanical properties using microfluidic bubble - Li, Zhen Guo (2014)
The rapid development of microfluidics plays a key role in the study of soft materials. Microfluidic systems provide several key advantages such as the precise control of the sample volume and the physico-chemical conditions. This doctorate thesis focuses on the theoretical and experimental study on soft materials, including water-in-oil droplets, cell membrane and high viscous liquids. Specially, droplet fusion, single-cell membrane poration and tensile strength measurement of liquids have been studied using microfluidic systems driven by laser-induced cavitation bubbles. Droplet fusion is demonstrated using a microfluidic chip actuated by a pulsed laser-induced cavitation bubble. The theoretical studies of the mechanism of the droplet fusion and the “neck” growth are carried out and a simplified model is established for the droplet generation using the microfluidic chip with a T-junction and a collection chamber. For droplet fusion, a cavitation bubble is created with the pulsed laser beam focused into one droplet. High-speed photography of the dynamics reveals that the droplet fusion is induced within a few tens of microseconds and caused by the rapid thinning of the continuous phase ﬁlm separating the droplets. Finally, the cavitation bubble collapses and re-condenses into the droplet. Droplet fusion is experimentally demonstrated for static and moving droplets, droplets of equal and unequal sizes, and droplets in the hexagonal structure. Furthermore, the diffusion is discussed for the fusing droplets and the transport is demonstrated for a single encapsulated cell into a fused droplet. Single-cell membrane poration is demonstrated using a microfluidic chip driven by a pulsed laser-induced cavitation bubble. The theoretical analyses of the microjet generation and the single-cell membrane poration due to the fast liquid microjet are carried out and a simplified model for single cell trapping is established. Based on the theoretical analyses, the microfluidic chip is designed with an array of single cell trapping structures and the single cell trapping is demonstrated. A laser-induced cavitation bubble is created at a quantified stand-off distance from the target cell. The asymmetrical growth and collapse of the cavitation bubble lead to the formation of the microjet, which deforms and porates the cell membrane. In the experiments, the membrane porations of myeloma cells are probed with the uptake of trypan blue. Time-resolved studies of the diffusion of trypan blue show a marked dependency on the bubble dynamics, i.e. the standoff distance. The penetration length of the dye increases with shorter distance. Numerical simulations of the diffusion process agree with larger pores formed on the cell membrane. The shock pressure and tensile strength measurement of water and glycerol is demonstrated using the laser-induced cavitation bubble in a microfluidic chip. The principle of the tensile strength measurement is theoretically analyzed. In the experiment, an air-liquid interface is created in a partially filled microchannel. A shock wave is generated by focusing an infrared pulsed laser into the liquid medium. Then, the expanding shock is reflected by the interface as a tensile wave and the liquid under the tension is ruptured. The shock pressures are determined by measuring the velocity of the interface and the tensile strength of water and glycerol are determined as -33.3 ± 2.8 MPa and -59.8 ± 10.7 MPa at 20 oC, respectively. The significant effects of the repetitive tensile strength, the microparticles and the surfactant on the cavitation nucleation are presented and discussed. The successful implementation of three microfluidic systems has evidenced the effectiveness of employing microfluidic systems driven by the pulsed laser-induced cavitation bubbles in the study of soft materials.